Development of turbulence model for high pressure natural gas transmission pipelines - Wang, Lingmeng (2017)
Currently, most electricity in Singapore is generated by imported natural gas via long-distance pipeline. Pipeline is the most traditional and commonly used way of transmission. But fatigue often occurs on the pipe wall due to the external interference and internal pressure fluctuations, leading to a leakage eventually. This is the biggest problem we are facing of gas transmission via pipeline. The first part of this dissertation discusses turbulent flow and vortex shedding phenomenon. And then the methods of turbulent modeling are reviewed, including Reynolds-averaged Navier-Stokes equation (RANS) based model, large eddy simulation (LES), direct numerical simulation (DNS) and Reynolds stress model (RSM). In this project, two cases are conducted to study the flows in pipe. One is focused on the vortex phenomenon. The main purpose of this case study is to determine the influence of dents on pipe wall. The other one is a simulation of a leaked pipe, aiming to investigate pressure and strain variation in the vicinity of leaking point, which are crucial parameter to detect leakage.